Impact of Formulation Choices on the Freeze-Drying of an Interleukin-6 Reference Material - Matejtschuk, Paul; Bird, Christopher; Ezeajughi, Ernest; MacLellan-Gibson, Kirsty; Wadhwa, Meenu (Frontiers in Molecular Biosciences, 2022)
Formulation is critical to successful delivery of lyophilised biologics. We have compared the impact of buffer choice and of the addition of sodium chloride (a formulant often viewed as unfavourable for freeze drying applications) on the outcome of trial lyophilization of an interleukin-6 reference material. While phosphate buffer was a preferred choice and yielded well-formed cakes associated with fair recovery of biological activity, the resultant residual moisture content was high (2-4%w/w). By inclusion of isotonic levels of NaCl, the freeze dried appearance and process was not impaired but the residual moisture delivered was considerably reduced to levels <1%w/w. We postulate that this is due to the presence of a more open cake structure and support this with evidence from thermal analysis and scanning electron microscopy. This work illustrates the importance of wide ranging empirical investigation of formulation options in order to optimise freeze drying outcomes for biologics.